Problematika Pengembangan Pariwisata Di Desa Wisata Tista, Kecamatan Kerambitan, Kabupaten Tabanan, Bali - Febriyani, Andini; Anom, I Putu; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p25, 2023)
Tista Tourism Village located in Tabanan Regency, Tista Tourism Village has cultural attractions that are different from other tourist villages, namely Legong Andir Tista, Tista Tourism Village also has beautiful nature on the trekking route with a stretch of rice fields and views of Mount Batukaru.. Tourism development is carried out to complete facilities and add tourist attractions so that they are more varied and increase the number of visits. As tourism activities progress in Tista Tourism Village, there are several issues that plague tourism development. This research was carried out in order to find out what are the problems that are hindering the development of tourism in the Tista Tourism Village. This study uses primary and secondary data. Data collection techniques were carried out through observation, interviews, documentation, and literature study. The technique of determining the sample used purposive sampling. The data analysis technique used is descriptive qualitative analysis Problems in tourism development in Tista Tourism Village are divided into two, namely physical problems and non-physical problems. Physical problems include the completeness of facilities and markets such as public toilets for tourists, a tourism icon which is still under construction, and the access road to the Dudu tourism icon which still needs improvement. Meanwhile, non-physical problems include marketing that has not been maximized, the use of social media owned by the Tista Tourism Village has not featured its tourism products, only sharing tourism activities in the Tista Tourism Village. Keywords: problems, tourism development, tourism villages